1980
DOI: 10.2466/pms.1980.51.3.699
|View full text |Cite
|
Sign up to set email alerts
|

Word Memory in Non-Psychotic Depression

Abstract: Two diverging explanations can be given for the fact that depressed persons often show deficits on verbal learning tasks: (a) researchers have suggested that memory deficits are the result of interference in the transfer from short- to long-term memory; (b) other researchers have suggested that depressives may not have cognitive deficits but may instead simply show deficits in performance. The present study assessed differences in recognition memory, free recall, organization in multitrial free recall, and fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…No difference was observed between the two states for short-term memory. Davis and Unruh (1980) found no memory deficits in nonpsychotic depressed outpatients compared with nondepressed psychiatric control outpatients on tasks that assessed recognition memory, free recall, and subjective organization. Rush, Weissenburger, Vinson, and Giles (1983) compared endogenous and nonendogenous depressives to adult norms on Vinson's (1973) neuropsychological exam.…”
Section: Processing Deficits In Depressionmentioning
confidence: 75%
See 2 more Smart Citations
“…No difference was observed between the two states for short-term memory. Davis and Unruh (1980) found no memory deficits in nonpsychotic depressed outpatients compared with nondepressed psychiatric control outpatients on tasks that assessed recognition memory, free recall, and subjective organization. Rush, Weissenburger, Vinson, and Giles (1983) compared endogenous and nonendogenous depressives to adult norms on Vinson's (1973) neuropsychological exam.…”
Section: Processing Deficits In Depressionmentioning
confidence: 75%
“…Subject selection procedures may have also been responsible for the results obtained by Davis and Unruh (1980). Unlike those investigations demonstrating a short-term memory deficit, Davis and Unruh (1980) examined outpatients rather than inpatients. The apparent contradictory findings of those studies may in fact be due to differences in severity of depressive illness, with inpatients being characterized by more severe forms of this disorder.…”
Section: Processing Deficits In Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, empirical evidence presented in the literature is far from supportive of this prediction. Salzman and Gutfreund (1986) provided a concise summary of effects of Decreased acquisition and recall of new information (Breslow et al, 1981;Cohenet al, 1982;Davis & Unruh, 1980;Friedman, 1964;Henry et al, 1973;Jarvik et al, 1972); increased emrsof omission (Henry et al, 1973;Jarviket al, 1972;McAllister, 1981;Whitehead, 1973); transposition errors, mispairing, and reversal of stimulus-response words (Henry et al, 1973;Whitehead, 1973); decreased ability to impose organization on unorganized information (Breslow et al, 1981;Weingartner et al, 1981Weingartner et al, , 1982; less effective coding and memory strategies (level of processing) (Breslow et al, 1981;Weingartner et al, 1981Weingartner et al, , 1982; fluctuating deficits in episodic memory; increased access to sad memories (Bower, 1981;Fogarty & Hemsley, 1983;Isenet al, 1978;Natale & Hantas, 1982;Teasdale & Fogarty, 1979) and, with increasing depression, decreased access to pleasant memories (Breslow et al, 1981); altered guessing strategies; taking fewer risks in a task (Miller & Lewis, 1977), reluctance to give oneself the benefit of the doubt (Alloy & Abramson, 1979), or reluctance to use negative feedback as a basis for change in strategy (Silberman et al, 1983); and decreased attention and reaction time (Breslow et al, 1981;Glass et al, 1981). The large number of studies that showed the detrimental effects of depression on cognition led Weingartner (1986) to conclude that every conceivable stage or type of information-processing system has been implicated in determining aspects of cognitive dysfunction in depres...…”
Section: The Effects Of Depression On Cognitive Performancesmentioning
confidence: 99%
“…The existence of memory deficits in depression is well substantiated (e.g. Cronholm & Ottosson, 1961;Sternberg & Jarvik, 1976;Cohen et al 1982;Breslow et al 1980;Frith et al 1983;Davis & Unruh, 1980;Koh & Wolpert, 1983;Calev & Erwin, 1985;Lang & Frith, 1981). However, these deficits are reported to be transient, disappearing in euthymic patients (e.g.…”
Section: Introductionmentioning
confidence: 99%